I have been banging my head against a wall trying to understand how-to make 'x' the subject of the following equation:
y = (w + x) / (x - 2)
I can't figure out how to make it appear as it does on the mock exam.
So far, I have the following steps:
y(x - 2) = w + x
xy - 2y = w + x
xy - x = w + 2y
And it's here where I get stuck. I just can't get my head around getting 'x' on its own.
Can someone please assist me?
You got it right so far and got through all what is difficult. You only need to factorise the x.
You know that:
Right? Well, do the same with x in your question, I'm sure you'll get it easily :)
x(y - 1) = w + 2y?
You're almost there. You can divide the (y-1)
Originally Posted by mcrilly
x = (w + 2y) / (y - 1)
Originally Posted by Esthephane